Surviving Utopia in Zone One - Cvek, Sven (Array, 2014)
In this article I offer a reading of Colson Whitehead’s novel Zone One (2011) in the context of contemporary speculative fictions of crisis. Following tentatively the tradition of “Gothic Marxism” the article focuses on the figure of the zombie in its contemporary, early-twenty first century articulation. My argument is twofold. First, I focus on the common recurrence of the zombie metaphor in descriptions of the state of today’s capitalist economy. In this context, Whitehead’s zombies function as morbid symptoms of the inability to imagine alternatives to the monstrosity of the existing reality. Second, I comment on the fact that the zombie metaphor is used to speak of the human consequences of capitalist development, thus enriching the repertoire of Gothic Marxism with this colonial image of enslavement. Considered in the context delineated above, Zone One appears “capitalist realist” in that the presence of zombies in the novel constantly precludes the possibility of any future-oriented action, and gives form to the contemporary failure of utopian imagination. The novel also makes a resigned step beyond the boundaries of capitalist realism, in that it argues that the economics of capitalism does not work, and depicts the consequences of existing capitalist relations as entirely destructive.